Ayurveda in Behavioral Addictions: Insights into Digital Dependency - Manishkumar Shrikant Yadav (Journal of Ayurveda, 2025)
Objective: The aim of the study was to explore Ayurveda’s potential in managing digital addiction (DA) through traditional interventions and holistic approaches. This study aims to provide a comprehensive review of Ayurvedic principles applied to behavioral addictions and their integration with modern de-addiction frameworks. Data Source: A systematic literature review was conducted using PubMed, Scopus, Google Scholar, and Ayurvedic texts such as Charaka Samhita and Sushruta Samhita. Relevant clinical trials, meta-analyses, and classical works were considered for analysis. Review Methods: Studies were selected based on relevance to DA pathophysiology and Ayurvedic interpretation. A systematic methodology was followed. Ayurvedic concepts of Doshic imbalances, mental health disorders, and integrative therapeutic strategies were emphasized. The protocol was registered with PROSPERO (CRD420251046180). Results: DA is closely associated with Vata and Pitta Dosha aggravation due to overstimulation and excessive screen exposure. Ayurveda interventions such as Nidana Parivarjana (avoiding causative agents), Pancakarma techniques, herbal preps like Brahmi and Ashwagandha, lifestyle routines such as Dinacarya, and Yoga-Pranayam enhance holistic recovery. The inclusion of Satvavajaya Cikitsa (cognitive behavioral strategies) aligns with modern de-addiction protocols, enhancing treatment efficacy. Conclusion: Ayurveda provides a complementary, mind–body framework for DA management; clinical studies are now needed to validate its efficacy and develop standardized treatment protocols.